Impacts of various amendments on the microbial communities and soil organic carbon of coastal saline–alkali soil in the Yellow River Delta - Liu, Runang; Liang, Beijia; Zhao, Huili; Zhao, Ying (Frontiers in Microbiology, 2023)
The utilization of industrial and agricultural resources, such as desulfurization gypsum and straw, is increasingly favored to improve saline alkali land. However, there is still a lack of comprehensive study on the mechanism of organic carbon turnover under the conditions of desulfurization gypsum and straw application. We studied the changes in soil chemical performance, microbial diversity, and microbial community structure in soils with the addition of various levels of straw (no straw, S0; low straw, Sl; medium straw, Sm; and high straw, Sh) and gypsum (no gypsum, DG0; low gypsum, DGl; and high gypsum, DGh) in a 120-day incubation experiment. The bacterial and fungal community richness was higher in the SmDGl treatment than in the SmDG0 treatment. The microbial community evenness showed a similar pattern between the SmDGl and SmDG0 treatments. The combination of the straw and desulfurization gypsum treatments altered the relative abundance of the main bacterial phyla Bacteroidetes and Firmicutes and the dominant fungal class Sordariomycetes, which increased with the enhancement of the SOC ratio. The combination of the straw and desulfurization gypsum treatments, particularly SmDGl, significantly decreased the soil pH and exchangeable sodium percentage (ESP), while it increased the soil organic carbon, microbial biomass carbon, and activities of soil enzymes. Improvement in the soil salinization environment clearly drove the changes in bacterial α-diversity and community, particularly those in the soil carbon fractions and ESP. In conclusion, these findings provide a strong framework to determine the impact of application practices on soil restoration, and the information gained in this study will help to develop more sustainable and effective integrated strategies for the restoration of saline–alkali soil.